Prevalence of comorbidities & risk factors for Multidrug Resistance among Tuberculosis patients in Institute of Respiratory Medicine, Kuala Lumpur / Alia Azmi - Azmi, Alia (2013)
Globally, the issue of Multidrug Resistant Tuberculosis (MDR-TB) was acknowledged as a threat to the successful prevention and treatment of TB. In Malaysia, TB remains a major health issue and incidence has been rising slowly for the past decade indicating poor success rate in current TB control programme. Currently, very little epidemiological data can be found regarding the situation of TB and MDR-TB in Malaysia. Therefore, this study aims to bridge the gap in information regarding TB and MDR-TB by identifying the population at risk. The objective of this study is also to identify the independent risk factors associated with MDR-TB in Malaysia. 477 TB patients from the Institute of Respiratory Medicine (IPR) were universally sampled based on the records of patients in 2010. Among 477 patients sampled, 67.9% were male with mean age 37.2 (SD 14.9). 30% of patients were foreign born with the majority were from Myanmar (14.9%), Indonesia (9.4%) and Bangladesh (2.7%). Prevalence of TB/HIV and TB/Diabetes among the patients sampled was 0.059 and 0.155 respectively. In multivariate analysis, BCG Status (AOR=0.292, 95%CI 0.13-0.67) was found to be a protective risk factor while history of previous TB (AOR=4.36, 95%CI 1.80-10.56) was a risk factor for MDR-TB.Whilst history of previous TB is a commonly acknowledged risk factor, the evidence of BCG as a protective factor for MDR-TB indicates that BCG vaccination is still a viable preventive measure. Association was found between BCG Status and foreign bom patients (p-value <0.01) indicating a need for active screening of immigrants.